DETERMINANTES E RESULTADOS DA INOVAÇÃO EM EMPRESAS DE CERÂMICA VERMELHA DE PRUDENTÓPOLIS - Antoneli, Gislaine Maier (2021)
Innovation is an essential component to the competitiveness and sustainability of organizations, not only for big companies, but it should also be for micro and small enterprises. That is because when small and micro enterprises establish innovative aspects, they strengthen their strategies, demonstrate market knowledge, create innovative attitudes of capacity, making them establish the competitiveness required in the market and, as a result, strengthen the region they are inserted. The capacity for innovation identifies the circumstances of expansion in the markets and makes use of more efficient methods of the existing resources. However, for the companies to enjoy the best practices, it is extremely important to learn about organizational methods, business management, and the relationship between the company and its internal and external agents. Thus, the general aim sought was to determine the internal and external factors related to the capacity for innovation of the Micro and Small Enterprises (MSE) in the sector of red pottery in the town of Prudentópolis, located in the Central-South region of the state of Paraná, in the light of the strategic theory of the Resource-Based View (RBV). The studied was developed in a descriptive character, with a quantitative approach comprising a convenience sample of 46 companies of the red pottery sector of the town. Two econometric models were proposed. One specified internal variables such as leadership, personnel management, information and knowledge, relationship with clients, relationship with society, and results. The other model was for external factors, where the following variables were used: government support, geographic location and base of external knowledge. Cronbach’s Alpha was employed to estimate the coherence of the answers to the questionnaire applied to the entrepreneurs. The t Test, F Test and the Coefficient of Determination (R2) were used to assess the significance of the exogenous variables and the determination power of the model, at the level of 95% of statistical confidence. For the model of internal factors, the variables that influenced the capacity for innovation were information and knowledge, relationship with clients and with society, and results. The model of external factors identified the influence of geographic location and the base of external knowledge. It is concluded that the researched MSE of the sector of red pottery in the town of Prudentópolis determine their capacity of innovation in association with internal and external factors. Nonetheless, not all the factors were significant. In the case of internal factors, the ones that stood out significantly were: access to information and knowledge, the relationship with clients and society (the results factor was not significant). In the case of external factors, geographic location and external knowledge were determining. Therefore, it was observed that it is necessary to focus efforts to developed leadership between entrepreneurs and managers, to align the programs that promote their employees’ training, and to identify what kinds of support are provided by the government, aiming at upgrading their management practices and increasing investment on new learning and new technologies